EFEKTIVITAS METODE PEMBELAJARAN PROJECT BASED LEARNING (PjBL) BERBASIS COLLABORATIVE LEARNING PADA MATA KULIAH MANAJEMEN PROYEK KONSTRUKSI - Susanto Susanto; Muhammad Ikbal; Mhd. Alfikar Marpaung (Nusantara Hasana Journal, 2026)
The low achievement of student competencies in the Construction Project Management course, driven by the imbalance between theoretical learning and field practice, serves as the foundation of this study. Such conditions necessitate the implementation of more active, contextual, and student-centered learning methods. This study aims to analyze differences in learning outcomes, perceptions, and collaborative skills among students, while simultaneously measuring the effectiveness of applying the Project-Based Learning (PjBL) method integrated with Collaborative Learning in the Construction Project Management course. A quantitative approach with a quasi-experimental design (one-group pretest-posttest) was employed, involving 15 students from the Vocational Education Program in Building Construction as the research sample. Data were collected through pretest and posttest instruments, Likert scale-based questionnaires, and observation sheets. Data analysis encompassed normality testing, homogeneity testing, paired sample t-test, and N-Gain calculations using SPSS. The findings revealed significant improvements across all variables: learning outcomes increased from a mean score of 67.00 to 89.00, student perceptions from 29.87 to 45.20, and collaborative skills from 34.40 to 44.47. A significance value of 0.000 (p < 0.05) confirmed that the alternative hypothesis was accepted. Furthermore, an N-Gain score of 0.72, classified within the high category, reinforces that the Collaborative Learning-based PjBL method is highly effective in promoting student learning improvement. Accordingly, this study provides a meaningful contribution to the development of collaborative project-based learning models in vocational education, while offering practical recommendations for lecturers in designing more contextual instructional strategies aligned with industry demands.